2016
DOI: 10.1111/sms.12719
|View full text |Cite
|
Sign up to set email alerts
|

Individual and combined effects of acute and chronic running loads on injury risk in elite Australian footballers

Abstract: A model that takes into account the current workload, and the workload the athlete has been prepared for, as an acute:chronic workload ratio has been previously used as a novel way to monitor training load and injury risk. Fifty-nine elite Australian football players from one club participated in this 2-year study. Global Positioning System technology was used to provide information on running workloads of players. An injury was defined as any non-contact "time-loss" injury. One-week (acute), along with 4-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 27 publications
5
78
3
Order By: Relevance
“…Although we did not identify any relationship between injury and monthly TL, acute:chronic workload ratio was a significant predictor of injury. This is similar to the relationship that has been consistently identified in adult athletes in multiple sports,13 14 43 44 and previously suggested as a useful metric to determine readiness to return to play 45. Although these studies suggested a protective effect of higher chronic TL, we did not find a positive or negative influence of monthly TL on injury.…”
Section: Discussionsupporting
confidence: 90%
“…Although we did not identify any relationship between injury and monthly TL, acute:chronic workload ratio was a significant predictor of injury. This is similar to the relationship that has been consistently identified in adult athletes in multiple sports,13 14 43 44 and previously suggested as a useful metric to determine readiness to return to play 45. Although these studies suggested a protective effect of higher chronic TL, we did not find a positive or negative influence of monthly TL on injury.…”
Section: Discussionsupporting
confidence: 90%
“…73 However, a significant body of evidence has emerged to demonstrate that high chronic training loads may protect athletes against injury. 27,41,54,[74][75][76][77] Collectively, these results suggest that training load might best be described as the "vehicle" that drives athletes toward or away from injury. 78 In the first study to demonstrate the protective effect of high training loads, Hulin et al 74 reported that cricket fast bowlers who bowled a greater number of balls over a 4-week period (ie, chronic training load) had a lower risk of injury than bowlers who bowled fewer balls.…”
Section: Athlete-load Monitoring and Injury Preventionmentioning
confidence: 97%
“…27,40 This analytical approach has recently been reported to identify injury risk in a variety of athletes. 27,54,55 However, while interesting for monitoring injury risk, the validity of the ACWR has recently been questioned 56,57 as the rolling average fails to account for the decaying nature of fitness and fatigue effects over time, and therefore it may not accurately represent variations in the manner in which loads are accumulated. An alternative method is to use an exponentially weighted moving average 58 for the calculation of acute and chronic loads, which assigns a decreasing weighting to compensate for the latency effects of loads.…”
Section: Analyzing Training-load Datamentioning
confidence: 99%
“…Recent studies indicate that high absolute loads may not be the problem per se, but rather excessive and rapid increases in the load that an athlete is exposed to relative to what he/she is prepared for, with evidence emerging from Australian football,150 152 175–177 basketball,178 cricket,116 179 football,180–182 rugby league122 183–185 and rugby union 127. Specifically, large week-to-week changes in load (rapid increases in intensity, duration or frequency) have been shown to place the athlete at a significantly increased risk of injury 45 127 152 175 177…”
Section: Load and Risk Of Injury In Athletesmentioning
confidence: 99%
“…However, these are highly inaccurate measures of load, as they fail to account for the intensity, movement repetitions or impact load performed. Recently, it has become increasingly popular to use global positioning system/microtechnology units to quantify running load, particularly in team sports 147 150–152 176 177 181–184 188. In certain individual sports such as cycling, the use of load sensors allows for composite measures incorporating training volume and intensity.…”
Section: Load and Risk Of Injury In Athletesmentioning
confidence: 99%